Alex - Alcala, José (Film director); Raynal, Marie; Salem, Lyes; Ruiz, Adrien (Gemini Films : Les Films de la Grande Ourse, 2005)
Alex is a young woman in her thirties who restores herself a ruins to the outskirts of a small town in the south of France. She sells fruits and vegetables in the markets and at night she works in the quarry, where she meets Karim. Alex has a fourteen-year-old son who lives with his father, and she now wants to get his custody. --